2017
DOI: 10.1097/igc.0000000000000962
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Lynch Syndrome in Women Presenting With Endometrial Carcinoma Under the Age of 50 Years

Abstract: All women with newly diagnosed EC should be assessed for inherited predisposition. Regional policies for assessment should be developed in accordance with available resources. Gynecologists are required to upgrade their skills in order to identify, assess, and counsel patients with suspected or established LS and appropriately refer to clinical genetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…One patient carried two mutations respectively in the BRCA1 and PMS2 genes with the phenotypes related to both LS and HBOC syndromes. The frequency of LS in our patients under 50 years of age was similar to that in a recent report from UK patients but higher than the frequency reported earlier in USA patients (9%) . This discordance might be explained by the difference in BMI between two ethnic populations.…”
Section: Discussionsupporting
confidence: 84%
“…One patient carried two mutations respectively in the BRCA1 and PMS2 genes with the phenotypes related to both LS and HBOC syndromes. The frequency of LS in our patients under 50 years of age was similar to that in a recent report from UK patients but higher than the frequency reported earlier in USA patients (9%) . This discordance might be explained by the difference in BMI between two ethnic populations.…”
Section: Discussionsupporting
confidence: 84%
“…MSI due to MLH1 hypermethylation was not identified in studies that performed MSI analysis alone. Eleven studies did not report data on MLH1 analysis, of which seven did not perform any MLH1 methylation analysis (Supplementary Table 2) [15,16,18,19,21,33,34,37,39,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The mean age and BMI were weighted based on the number of patients per study. Four studies had inclusion criteria of patients less than 50-year old, and therefore were excluded from calculation of mean age [15][16][17][18]. Only studies that reported a number of patients with a mean age/ BMI value were included in calculation of mean age and BMI for each group.…”
Section: Strategy For Search and Selection Criteriamentioning
confidence: 99%
“…The mean age at diagnosis was 41.6 years. In another study by Anagnostopoulos et al (22), MMR germline mutation test was performed and they identified 3 pathogenic MMR mutations in 3 of 35 patients with endometrial cancer under age 50 (8.5%; 3/35).…”
Section: Discussionmentioning
confidence: 99%